Pemanfaatan media crocodile physics dalam pembelajaran untuk meningkatkan pemahaman konsep fisika - Siwi Puji Astuti; Alhidayatuddiniyah TW; Santy Handayani (Navigation Physics : Journal of Physics Education, 2019)
Learning media is a communication tool both print and audiovisual that is used to convey the material that will be delivered by educators to students in the learning process. The use of media as learning should receive special attention from educators in each learning process. If the media as a learning tool used is very interesting, it does not rule out the possibility that students will better understand the concepts that will be delivered in the learning process to the fullest. Media that can be used in learning physics one of which is Crocodile Physics. This research was conducted to determine the positive effect of using Crocodile Physics media in learning on understanding physics concepts. The study was conducted at Indraprasta PGRI University in 2018. The population is the first semester students of the 2018/2019 academic year. The researcher used quantitative research methods. The experimental design used is classical experimental design. The data analysis technique used is the Independent sample t-test using the SPSS 16 program. The research hypothesis to be tested is that there is a positive influence on the use of Crocodile Physics media in learning to understand physics concepts. The results of the calculation of the study have a sig value of 0.00 < 0.05 which states that there is a positive influence on the use of Crocodile Physics media in learning towards understanding physics concepts. Therefore the results of the study state that there is a positive influence on the use of Crocodile Physics media in learning towards understanding physics concepts.